Recent Advances in Antenna Design for 5G Heterogeneous Networks - Elfergani, Issa Tamer; Abd-Alhameed, Raed A; Hussaini, Abubakar Sadiq (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this book is to highlight up to date exploited technologies and approaches in terms of antenna designs and requirements. In this regard, this book targets a broad range of subjects, including the microstrip antenna and the dipole and printed monopole antenna. The varieties of antenna designs, along with several different approaches to improve their overall performance, have given this book a great value, in which makes this book is deemed as a good reference for practicing engineers and under/postgraduate students working in this field. The key technology trends in antenna design as part of the mobile communication evolution have mainly focused on multiband, wideband, and MIMO antennas, and all have been clearly presented, studied and implemented within this book. The forthcoming 5G systems consider a truly mobile multimedia platform that constitutes a converged networking arena that not only includes legacy heterogeneous mobile networks but advanced radio interfaces and the possibility to operate at mm wave frequencies to capitalize on the large swathes of available bandwidth. This provides the impetus for a new breed of antenna design that, in principle, should be multimode in nature, energy efficient, and, above all, able to operate at the mm wave band, placing new design drivers on the antenna design. Thus, this book proposes to investigate advanced 5G antennas for heterogeneous applications that can operate in the range of 5G spectrums and to meet the essential requirements of 5G systems such as low latency, large bandwidth, and high gains and efficiencies.